MODEL STRUCTURE OF FUNCTIONAL SOCIAL CAPITAL - THERON, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the problem of the functionality of social capital as an important social resource for the development of society and the economy. On the basis of a multidisciplinary approach, the essence of functionality as a whole set of performed functions and roles of social capital in the space of its development is substantiated. It is shown that the variability of the functional structure is determined by certain factors — arguments, such as elements of the structure, properties, sources of social capital formation, features of the global environment of functioning and development, goals of individual and group social subjects of carriers of social capital, etc. The model structure of the functionality of social capital is characterized in the composition of resource, competitive, value (ethical), communicative (interactive) functions, functions of socialization, identification, social integration, adaptation, optimization of management and coordination of interaction, socio-economic security and socio-psychological stability, functions the formation of civil society (active citizenship) and social responsibility, the function of tolerance. It is shown that the amount of social capital of the group is a function of the number of group members, the level of group identification, the number of interpersonal interactions in the group, the amount of individual social capital, intragroup factors, macroeconomic influence of the external environment; of the synergistic effect of uniting social subjects into a group, M. Ringelman’s effect. In summary, it has been shown that the function of social capital is a mechanism of social multiplier-accelerator according to its purpose. The completeness and balance of the implementation of the entire functional spectrum of social capital together with the quality and productivity of its forms and types determine the effectiveness and dynamics of civilizational progress. The research used methods of monographic, scientific generalization, analysis and synthesis, structural and functional.